One Label or Two? Linguistic Influences on the Similarity Judgment of Objects between English and Japanese Speakers - Masuda, Takahiko; Ishii, Keiko; Miwa, Koji; Rashid, Marghalara; Lee, Hajin; Mahdi, Rania (Frontiers in Psychology, 2017)
Recent findings have re-examined the linguistic influence on cognition and perception, while identifying evidence that supports the Whorfian hypothesis. We examine how English and Japanese speakers perceive similarity of pairs of objects, by using two sets of stimuli: one in which two distinct linguistic categories apply to respective object images in English, but only one linguistic category applies in Japanese; and another in which two distinct linguistic categories apply to respective object images in Japanese, but only one applies in English. We conducted four studies and tested different groups of participants in each of them. In Study 1, we asked participants to name the two objects before engaging in the similarity judgment task. Here, we expected a strong linguistic effect. In Study 2, we asked participants to engage in the same task without naming, where we assumed that the condition is close enough to our daily visual information processing where language is not necessarily prompted. We further explored whether the language still influences the similarity perception by asking participants to engage in the same task basing on the visual similarity (Study 3) and the functional similarity (Study 4). The results overall indicated that English and Japanese speakers perceived the two objects to be more similar when they were in the same linguistic categories than when they were in different linguistic categories in their respective languages. Implications for research testing the Whorfian hypothesis and the requirement for methodological development beyond behavioral measures are discussed. (243 words)